Factors Affecting Behaviors of Caregiver to Tuberculosis Patients at Amphur Banchang, Rayong Province - ภัทรกุลพงษ์ กิจชัย (Disease Control Journal, 2007)
Thepurpose of this study was to describe the natural history of tuberculosis patients and to identify factors predicting behavior of caregivers at Banchang Hospital, Rayong province. The data was collected from August 1, 2007-September 30, 2007 using questionnaires. The results of study were as follows: 62% of Tuberculosis patients were male, 42% was 20-39 years old and 55% was more than 40 years old. Seventy nine percent were from low income economic group (< 6000 bht). The caregivers, 68% were female and 40% were their wives or their husbands. The other caregivers, 60% were their cousins. The caregivers had average score 83 % of knowledge for caring tuberculosis patients. The relationship between patients and caregivers were high, the caregiver burden scales were medium.The social support scale average score were medium but have high score for doctors and nurses supporting them. The correlation of knowledge scale and behaviors of caregivers was low and not significant( r =0.205 p=0.117). The factors significantly correlated with tuberculosis patients caring behaviors of caregivers were relationship between them(r =0.329 p=0.01) and social support (r =0.654 p=0). The caregiver burden scale was not correlate with behaviors of caregivers (r = -0.108 p=0.411). Some important findings could be drawn from this study: relationship of caregivers, the social support, feeling sympathy and paying more attention to both tuberculosis patients and their families, in particular if all these interventions were from doctors and nurses, having a significant correlation to qualify of caring to tuberculosis patients by the caregivers.